Diversification rates, host plant shifts and an updated molecular phylogeny of Andean Eois moths (Lepidoptera: Geometridae) - Strutzenberger, Patrick; Brehm, Gunnar; Gottsberger, Brigitte; Bodner, Florian; Seifert, Carlo Lutz; Fiedler, Konrad (PloS one, 2017)
Eois is one of the best-investigated genera of tropical moths. Its close association with Piper plants has inspired numerous studies on life histories, phylogeny and evolutionary biology. This study provides an updated view on phylogeny, host plant use and temporal patterns of speciation in Eois. Using sequence data (2776 bp) from one mitochondrial (COI) and one nuclear gene (Ef1-alpha) for 221 Eois species, we confirm and reinforce previous findings regarding temporal patterns of diversification. Deep diversification within Andean Eois took place in the Miocene followed by a sustained high rate of diversification until the Pleistocene when a pronounced slowdown of speciation is evident. In South America, Eois diversification is very likely to be primarily driven by the Andean uplift which occurred concurrently with the entire evolutionary history of Eois. A massively expanded dataset enabled an in-depth look into the phylogenetic signal contained in host plant usage. This revealed several independent shifts from Piper to other host plant genera and families. Seven shifts to Peperomia, the sister genus of Piper were detected, indicating that the shift to Peperomia was an easy one compared to the singular shifts to the Chloranthaceae, Siparunaceae and the Piperacean genus Manekia. The potential for close co-evolution of Eois with Piper host plants is therefore bound to be limited to smaller subsets within Neotropical Eois instead of a frequently proposed genus-wide co-evolutionary scenario. In regards to Eois systematics we confirm the monophyly of Neotropical Eois in relation to their Old World counterparts. A tentative biogeographical hypothesis is presented suggesting that Eois originated in tropical Asia and subsequently colonized the Neotropics and Africa. Within Neotropical Eois we were able to identify the existence of six clades not recognized in previous studies and confirm and reinforce the monophyly of all 9 previously delimited infrageneric clades.
Keywords: Plants; Species Specificity; Moths; DNA; South America; Electron Transport Complex IV; Jižní Amerika; Animals; respirační komplex IV; druhová specificita; Phylogeny; zvířata; fylogeneze; rostliny; můry